2019
DOI: 10.1016/j.chembiol.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Genetic-Code Expansion with Bulky Lysine Derivatives by an Engineered Pyrrolysyl-tRNA Synthetase

Abstract: Highlights d A mutant pyrrolysyl-tRNA synthetase, PylRS(Y306A/Y384), acts on diverse amino acids d The PylRS mutant and tRNA Pyl incorporated 17 non-natural amino acids into proteins d Crystal structures of the PylRS mutant bound with 14 of the amino acids were solved d This information will facilitate the structure-based design of novel amino acids

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 84 publications
0
57
0
Order By: Relevance
“…To better understand OABKRS′s efficient incorporation of MPABK , as well as the binding modes of PABK , MOABK , and MPABK to their respective synthetases, we conducted a docking study using AutoDock Vina (Supporting Information). Modeling revealed that MPABK ′s side chain is kinked such that the benzylic methyl group fits into a space at the top of the tunnel, and the para ‐azido substituent is accommodated facing outward in the pocket toward D373 (Figure S4 A and D), nearly identically to the azide in a published co‐crystal structure of meta ‐azido‐ N ϵ ‐Cbz‐Lys in OABKRS . PABK ′s azide group is positioned similarly.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…To better understand OABKRS′s efficient incorporation of MPABK , as well as the binding modes of PABK , MOABK , and MPABK to their respective synthetases, we conducted a docking study using AutoDock Vina (Supporting Information). Modeling revealed that MPABK ′s side chain is kinked such that the benzylic methyl group fits into a space at the top of the tunnel, and the para ‐azido substituent is accommodated facing outward in the pocket toward D373 (Figure S4 A and D), nearly identically to the azide in a published co‐crystal structure of meta ‐azido‐ N ϵ ‐Cbz‐Lys in OABKRS . PABK ′s azide group is positioned similarly.…”
Section: Resultsmentioning
confidence: 95%
“…This is one of the most versatile PylRS mutants for incorporating sterically demanding lysine derivatives; the Y349F mutation increases aminoacylation kinetics and yield, while Y271A exposes a deep hydrophobic pocket in the PylRS catalytic site that accommodates benzyl carbamates . This synthetase incorporated MOABK as well (Figure S3), but produced only modest protein yields with PABK (Figure S2 A) . A PylRS mutant with L274A, C313A, and Y349F mutations was significantly more efficient at accepting PABK as a substrate (Figure S2 B) and was termed PABKRS .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Site-saturation mutagenesis (SSM) via NNK codons (N: A/T/C/G; K:G/T) was used to specifically randomize chosen positions of the aaRS [ 23 ]. Our strategy is further based on an analysis of the available high-resolution molecular structure of Mm PylRS, as well as earlier reports showing that mutagenesis of the crucial positions N346 and C348 ( Figure 2 ) is feasible to expand the substrate range of this enzyme [ 24 , 25 ]. We make a step further and include other residues in our mutagenesis schemes, importantly including second and higher shell residues, which are expected to be important for ncAA substrate binding and recognition, but not in direct contact.…”
Section: Introductionmentioning
confidence: 99%